Pengetahuan, Sikap dan Dukungan Keluarga terhadap Niat Memeriksakan Dahak pada Presumtif TBC - Nike Indah Arodah; Noor Alis Setiyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the relationship between knowledge, attitudes, and family support on the intention to have sputum examined in a group suspected of having tuberculosis in the Margoyoso II Health Center. The research method used in this research is quantitative. The design in this study is analytic with a cross sectional approach. The results showed that of the 113 respondents who had low knowledge about tuberculosis, 44 (67.7%) had a low attitude towards sputum examination, 47 (65.3%), and 55 (85.9%) had a low level of family support. Results The knowledge variable has a p value of 0.003, attitude has a p value of 0.006, family support has a p value <0.0001. The results of the probability variables of knowledge, attitudes, and family support are smaller than the significant level of 5% (0.05), meaning that it can be concluded that there is a relationship related to knowledge, attitudes, and family support on the intention to check sputum in the suspected tuberculosis group in the Work Area of ​​the Margoyoso II Health Center . Keywords: Attitude, Family Support, Knowledge, Sputum Examination, Tuberculosis